Effects of National Culture on Earnings Quality of Banks - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2011)
We examine the relation between four dimensions of national culture and earnings quality of banks using a sample of banks from 39 countries. Our main analysis, which focuses on the pre-financial crisis period 1993–2006, indicates that banks in high individualism, high masculinity, and low uncertainty avoidance societies manage earnings to just-meet-or-beat the prior year's earnings. In tests of income smoothing through loan loss provisions, we find that banks in high individualism, high power distance, and low uncertainty avoidance societies report smoother earnings. Our exploratory analysis of the effects of national culture on accounting outcomes during the financial crisis period 2007–2008 indicates that cultures that encourage higher risk-taking experienced more bank troubles in the form of larger losses or larger loan loss provisions.